Systems leadership in practice: thematic insights from three public health case studies - Charlotte Bigland; David Evans; Richard Bolden; Maggie Rae (BMC, 2020)
Abstract Background 'Systems leadership' has emerged as a key concept in global public health alongside such related concepts as 'systems thinking' and 'whole systems approaches.' It is an approach that is well suited to issues that require collective action, where no single organisation can control the outcomes. While there is a growing literature on the theory of systems leadership in a number of fields, there remains a lack of published empirical studies of public health systems leadership for professionals to learn from. The aim of the current project was to conduct cases studies in UK public health to provide empirical evidence on the nature of effective systems leadership practice. Methods Three system leadership case studies were identified in the key domains of public health: health protection, healthcare public health and health improvement. A total of 27 semi-structured interviews were conducted. Data were thematically analysed to identify the components of effective systems leadership in each case and its impact. Results The thematic analysis identified themes around 'getting started,' 'maintaining momentum' and 'indicators of success' in systems leadership. In terms of getting started, the analysis showed that both a compelling 'call to action' and assembling an effective 'coalition of the willing' are important. To maintain momentum, the analysis identified themes relating to system structure, culture and the people involved. Regarding culture, the main themes that emerged were the importance of nurturing strong relationships, curiosity and a desire to understand the system, and promoting resilience. The analysis identified three components that could be used as indicators of success; these were a sense of enjoyment from the work, resource gains to the system and shifts in data indicators at the population level. Conclusions This study has provided insight into the nature of systems leadership in public health settings in the UK. It has identified factors that contribute to effective public health systems leadership and offers a thematic model in terms of establishing a systems leadership approach, maintaining momentum and identifying key success indicators.